Unconditional Accumulation of Nonclassicality in a Single‐Atom Mechanical Oscillator. Issue 11 (27th May 2020) - Podhora, Lukáš; Pham, Tuan; Lešundák, Adam; Obšil, Petr; Čížek, Martin; Číp, Ondřej; Marek, Petr; Slodička, Lukáš; Filip, Radim
Abstract: The robust experimental accumulation of nonclassicality of motion of a single trapped ion is reported. The nonclassicality stems from deterministic incoherent modulation of thermal phonon number distribution implemented by a laser excitation of nonlinear coupling between the ion's internal—electronic levels and external—motional states. It is demonstrated that the repetitive application of this nonlinear process monotonically accumulates the observable state nonclassicality. The output states converge to a phonon number distribution with high overlap with a particular Fock state and visible quantum non‐Gaussian aspects including corresponding negative Wigner function. The resulting oscillator states prove deterministic transition in the hierarchy of quantum non‐Gaussianity up to four phonons. This transition is very robust against experimental imperfections and produces increasing entanglement potential. Abstract : Nonclassicality is created using a nonlinear coupling between mechanical motion and electronic transition of a single trapped ion. The repetitive applications of the interaction result in unconditional monotonous accumulation of the nonclassicality and quantum non‐Gaussianity. The phonon number distributions converge to a selectable Fock state with corresponding negative Wigner function for any initial thermal energy of the atomic oscillator.